Impact of transglutaminase treatment given to the skim milk before or after microfiltration on the functionality of micellar casein concentrate used in process cheese product and comparison with rennet casein. (May 2022) - Salunke, P.; Metzger, L.E.
Abstract: The objective of the study was to evaluate the impact of transglutaminase (TGase) on the functionality of micellar casein concentrate (MCC) when used in process cheese product (PCP) applications. In this study, the impact of TGase treatment of skim milk prior to microfiltration (MF) as well as TGase treatment of retentate after MF was evaluated. The treatment included TGase treatment prior to MF (T1); control without enzyme (C1); TGase after MF (T2); and a control without enzyme (C2). Best treatment was also compared with the PCP sample made using rennet casein (RCN). The CGE analysis indicated heavy crosslinking in T2 than in T1. The TGase treatment modified the viscosity, hardness and melt characteristics of PCP compared with the control and RCN PCP samples. This study demonstrated that TGase treatment modifies the functional properties (unmelted and melted) of MCC when used as an ingredient in PCP.